BIM-based model for sustainable built environment in Saudi Arabia - Hasanain, Fatma A.; Nawari, Nawari O. (Frontiers in Built Environment, 2022)
BIM has had a significant influence on the building and construction industry, contributing to efficiency, productivity, and cost-effectiveness improvements. BIM technology’s integrative nature makes it a perfect platform for adopting sustainable techniques in new construction, renovation, and retrofitting of existing structures. Saudi Arabia’s market gasoline prices fell drastically between 2018 and 2020, forcing the Kingdom to create its 2030 vision. The 2030 vision seeks to transform the Kingdom of Saudi Arabia (KSA) into an ideal sustainable society by lowering its dependency on oil and constructing more sustainable buildings and infrastructures. The number of green buildings and high-performance buildings in the KSA is inadequate, and the rate of change is too slow. Due to KSA’s need to enhance its built environment, it established a new green building rating named “Mostadam.” Currently, there is no metric to measure the roadmap to achieve the aspects of the KSA’s 2030 vision, and the number of green buildings in the KSA is very low compared to other countries. Therefore, there is an urgent need to translate the KSA’s green objectives into effective regulations. To attain this goal, there must be uniformity across jurisdictions in order to make sound and well-informed decisions about adopting and enforcing sustainability. This research intends to focus on the advanced capability of using BIM and creating a BIM-Based model to help facilitate the green building certification in Saudi Arabia that supports its vision of 2030. The research proposes a new strategy based on the integration of BIM and Mostadam green building rating systems where a BIM plug-in can aid in achieving the 2030 envisioned water sustainability goal and implement sustainable design principles in Saudi Arabia. Autodesk Revit and Dynamo were used for programming and visualizing the model. The model focused on one main category of Mostadam’s Green Building Rating System: water conservation. This study used a mixed methodology that combines qualitative and quantitative approaches. Phase I of this study focuses on the literature review and collection of available data about BIM, Green Building Rating Systems, and the KSA 2030 vision. Phase II aims at collecting data from an online survey sent to AEC professionals. Moreover, phase II of this study includes developing a BIM-Based model using Autodesk Revit and Dynamo. Phase III embraces the validation of the model using a prototype and a case study. Driven from the data collected, the new BIM-Based model assisted in achieving the KSA 2030 vision by reducing the water consumption when compared to the baseline water consumption. The model’s constraints are presented along with future phases of the study.